Enhancing Sleep Quality in Hypertensive Patients Through Slow Stroke Back Massage: A Family Nursing Care Approach - Arum Nur Arista; Minarti Minarti; Dwi Adji Norontoko; Aida Novitasari (Alta Dharma Publisher, 2026)
Introduction: Hypertension is a prevalent condition among the elderly, often leading to poor sleep quality. Objective: This case study aimed to describe the effect of Slow Stroke Back Massage (SSBM) combined with family nursing care in improving sleep quality among elderly hypertensive patients. Method: This descriptive case study involved two elderly hypertensive patients receiving family nursing care at Puskesmas Tambak Wedi, Surabaya. The intervention consisted of SSBM performed for 30 minutes every two days for a week. Data were collected through observation, interviews, and the Pittsburgh Sleep Quality Index (PSQI). Results: Both patients showed improved sleep quality, as indicated by decreased PSQI scores (from 14 to 5 and from 16 to 6) and better blood pressure control. These findings describe individual improvements observed in two cases. Recommendation: Slow Stroke Back Massage can be considered a supportive nursing intervention within family care. However, as this study involved only two participants, the findings are not generalizable and should be interpreted as case-based observations